2017
DOI: 10.17305/bjbms.2017.2279
|View full text |Cite
|
Sign up to set email alerts
|

Safety of once- or twice-daily dosing of non-vitamin K antagonist oral anticoagulants (NOACs) in patients with nonvalvular atrial fibrillation: A NOAC-TR study

Abstract: Once-daily dosing of non-vitamin K antagonist oral anticoagulants (NOACs) may increase patient adherence to treatment but may also be associated with a higher risk of bleeding. In this study, we investigated the adherence to once- or twice-daily dosing of NOACs and the risk of bleeding in nonvalvular atrial fibrillation (NVAF) patients. This multicenter cross-sectional study, conducted between 1 September 2015 and 28 February 2016, included 2214 patients receiving NOACs for at least 3 months, due to NVAF. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
9
0
1
Order By: Relevance
“…However, it was pointed out that a once‐daily regimen had greater peak‐to‐trough blood levels, which may increase the risk of bleeding 21 . The NOAC‐TR study, 22 which examined adherence to a once‐ or twice‐daily regimen of DOACs, showed that a once‐daily regimen contributed to better adherence, although there was no difference in the incidence rate of bleeding. In addition, when switching and discontinuation rates were examined separately in the present study, only switching rates differed among DOACs.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was pointed out that a once‐daily regimen had greater peak‐to‐trough blood levels, which may increase the risk of bleeding 21 . The NOAC‐TR study, 22 which examined adherence to a once‐ or twice‐daily regimen of DOACs, showed that a once‐daily regimen contributed to better adherence, although there was no difference in the incidence rate of bleeding. In addition, when switching and discontinuation rates were examined separately in the present study, only switching rates differed among DOACs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that other risk factors may independently affect nonadherence, and the combined action of these factors is necessary for the development of bleeding complications. 89 …”
Section: Introductionmentioning
confidence: 99%
“…In our study, the incidence of ischemic stroke in the good compliance group was lower than that in the poor compliance group, and the stroke degree of the 3 patients in the good compliance group was lower than that of the 12 patients in the poor compliance group. Moreover, Pearson correlation analysis showed that the compliance of NOACs in NVAF patients was negatively correlated with the severity of ischemic stroke [ 17 ]. These indicate that active and effective treatment with NOACs is an independent protective factor for effectively reducing the severity of ischemic stroke [ 18 ].…”
Section: Discussionmentioning
confidence: 99%